Assessment of indoor air exposure at residential homes: Inhalation dose and lung deposition of PM(10), PM(2.5) and ultrafine particles among newborn children and their mothers - Madureira, J (2020)
Accurate assessment of particulate matter (PM) dose and respiratory deposition is essential to better understand the risks of exposure to PM and, consequently, to develop the respective risk-control strategies. In homes, this is especially relevant in regards to ultrafine particles (UFP; <0.1 μm) which origin in these environments is mostly due to indoor sources. Thus, this study aimed to estimate inhalation doses for different PM mass/number size fractions (i.e., PM10, PM2.5 and UFP) in indoor air of residential homes and to quantify the deposition (total, regional and lobar) in human respiratory tract for both newborn children and mothers. Indoor real-time measurements of PM10, PM2.5 and UFP were conducted in 65 residential homes situated in Oporto metropolitan area (Portugal). Inhalation doses were estimated based on the physical characteristics of individual subjects and their activity patterns. The multi-path particle dosimetry model was used to quantify age-specific depositions in human respiratory tract. The results showed that 3-month old infants exhibited 4-fold higher inhalation doses than their mothers. PM10 were primarily deposited in the head region (87%), while PM2.5 and UFP depositions mainly occurred in the pulmonary area (39% and 43%, respectively). Subject age affected the pulmonary region and the total lung deposition; higher deposition being observed among the newborns. Similarly, lower lobes (left lobe: 37% and right lobe: 30%) received higher PM deposition than upper and middle lobes; right lobes lung are prone to be more susceptible to respiratory problems, since asymmetric deposition was observed. Considering that PM-related diseases occur at specific sites of respiratory system, quantification of site-specific particle deposition should be predicted in order to better evidence the respective health outcomes resulting from inhaled PM.